Epistemologi Revolusi Ilmiah Thomas Kuhn (Pemikiran dan Relevansinya Terhadap Kajian Keilmuan Islam): Pemikiran dan Relevansinya Terhadap Kajian Keilmuan Islam - Rahmat Ramadhan, Rajendra; M. Guntur Sandi Pratama; Valid Fathony , Bimba (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
Thomas Kuhn is a philosopher and scientist who is unique in giving names to the terms he uses in his scientific models. Kuhn used the term "revolution", to represent a name for development in science which is a discourse in the sense of emphasizing alternatives such as politics. Thomas Kuhn's ideas are interesting for discussion among academics and the development of modern philosophy. This research is a type of library research, namely research whose object of study uses library data in the form of books as the data source. Kuhn's thinking was a rebellion against the positivism paradigm (as was also done by Karl Raimund Popper, Paul Feyerabend, or Stephen Toulmin). Kuhn's ideas were very radical and contributed greatly to post-positivism and postmodern epistemology with its pluralism of scientific paradigms. Thomas Kuhn's thought regarding the "Scientific Revolution" is the idea of ​​a drastic change in knowledge, so that this process is said to be a breakthrough for the "history of science" itself. Starting from a paradigm that becomes a worldview for humans in viewing "knowledge" and is processed into knowledge ready to be tested and criticized. As time goes by, intellectual development among Muslims can borrow from Western civilization to advance Islamic sciences. Because Islam does not cover knowledge.